STRATEGI PEMBENTUKAN SOFT SKILL SANTRI DI PONDOK PESANTREN MAMBAUL ULUM PUTRI BATA-BATA PAMEKASAN - Rohelah Hasin; Saiful Hadi (re-JIEM (Research Journal of Islamic Education Management), 2019)
This research is aimed at finding out the treasure of knowledge in Islamic boarding schools (Pesantren) about practices of the establishment of Santri’s soft skill through daily life trainings. Those training could be in the form of the activities of ibadah mahdoh, ibadah ghoiru mahdoh, and other learning activities. The approach of this study uses qualitative approach with phenomenological plans. The result of this study shows that (1) habituating strategy through the boarding school activities namely Santri are joining all activities by obeying the rule with strict supervision and giving punishmet to them who disobey it. Meanwhile, the soft skills appear among the santri are disciplinary, honesty, responsibility, self motivation, self confidence, communicating, and leadership. (2) The obstacles which frequently appear among them are “the minimum of Santri’s enthusiasm in forming the self skills so that their enthusiasm appears in joining the activities of establishing Santri’s soft skills and the supporting factor is the masyaikh’s pretension to make all santri have life skill.